Respiratory Component of the Orienting Reflex: A Novel Sensitive Index of Sensory-Induced Arousal in Rats - Nalivaiko, Eugene; Bondarenko, Evgeny; Lidstrom, Andreas; Barry, Robert J. (Frontiers in Physiology, 2012)
In humans, the integrated response to a novel stimulus (orienting reflex) includes behavioral (head turning etc) and well-characterized physiological components (changes in heart rate, respiration, skin conductance, and EEG patterns). In rodents, the physiological components of the orienting reflex include changes in heart rate and cutaneous vasoconstrictor tone, but respiratory changes have so far not been systematically documented. In the present study conducted in adult male Wistar rats, the orienting reflex was elicited by 60-dB acoustic tones while animals were in a whole-body plethysmograph for respiratory recordings. In addition to respiration, in different groups of animals we concurrently recorded either EEG, or heart rate (both by biotelemetry), or tail blood flow (using ultrasound Doppler). Acoustic stimuli provoked vigorous tachypnoeic responses with respiratory rate rising from 80-100 to 450-650 cpm, and with small and variable changes in tidal volume. This respiratory arousal response was often, but not always, accompanied by EEG desynchronization and by variable tail vasoconstriction, and by small and inconsistent changes in the heart rate. We conclude that tachypnoeic responses are a new highly sensitive index of sensory-induced arousal.